2009
DOI: 10.1021/ar800174z
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Metal Complex Optical Probes: Targeted and Responsive Systems Based on Lanthanide Luminescence

Abstract: To understand better the structure and function of biological systems, cell biologists and biochemists would like to have methods that minimally perturb living systems. The development of emissive optical probes is essential for improving our observation of intracellular signaling and recognition processes. Following excitation of the probe, photons emitted from the probe may be observed by spectroscopy or microscopy and encode information about their environments in their energy, lifetime, and polarization. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
484
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 674 publications
(492 citation statements)
references
References 48 publications
6
484
0
2
Order By: Relevance
“…The lanthanide luminescence microscopy studies had shown the well-defined punctate vesicular distribution profile, possibly associated with lysosomal localization, as seen previously with Ln(III) complexes of related structure and overall complex charge. 23 Therefore, it is reasonable to speculate that confinement within vesicles restricts the exchange of water molecules that can access the paramagnetic metal center. Such a "relaxation quenching" effect has already been reported by Aime and co- workers 30,31 and has been interpreted in terms of a three compartment relaxation model.…”
mentioning
confidence: 99%
“…The lanthanide luminescence microscopy studies had shown the well-defined punctate vesicular distribution profile, possibly associated with lysosomal localization, as seen previously with Ln(III) complexes of related structure and overall complex charge. 23 Therefore, it is reasonable to speculate that confinement within vesicles restricts the exchange of water molecules that can access the paramagnetic metal center. Such a "relaxation quenching" effect has already been reported by Aime and co- workers 30,31 and has been interpreted in terms of a three compartment relaxation model.…”
mentioning
confidence: 99%
“…Among all sensing technologies, photon‐signal‐based biosensors such as organic dyes,1, 2, 3, 4 metal complexes,5, 6, 7, 8, 9, 10 and semiconductor nanocrystals11 are the most commonly used ones. However, these probes have several limitations in detection or sensing.…”
Section: Introductionmentioning
confidence: 99%
“…These polynucleotides are of interest for any 21 biological application in which the expression of proteins is beneficial. The main obstacle to 22 the wide-spread use of these pDNA and mRNA based therapies is the low efficiencies obtained 23 with the current transfection methods. Negatively charged nucleic acids are mostly complexed 24 with positively charged carriers to enhance cellular uptake of the complexes which are formed.…”
mentioning
confidence: 99%
“…Also, the often cationic fluorophores lower the overall negative charge of the 20 polynucleotides which might interfere with the intracellular migration behavior of nucleic acids, 21 complexation with and dissociation from cationic carrier. 22 Incorporation of modified nucleotides 23 Apart from the labeling strategies mentioned above, another popular commercially available 24 option is the in vitro incorporation of modified nucleotides into the polynucleotide backbone. 25 The term "modified" stands for a nucleotide that differs from the naturally occurring 26 nucleotides through the addition of a functional moiety.…”
mentioning
confidence: 99%